25-Hydroxyvitamin-D levels in Sjögren’s syndrome: is it the right time to dismiss the case or not? - Karabulut Gonca; Yilmaz Zevcet; Yildirim Simsir Ilgin; Barutcuoglu Burcu; Tanigor Goksel (Türk Biyokimya Dergisi)
This study aimed to investigate whether patients with primary Sjögren syndrome (SjS) have different levels of 25 OH-D3 (vitamin D) when compared to healthy populations and whether differences in 25 OH-D3 correlated with disease activity or markers.